Study on embryotropic effects of the supramolecular complex of ivermectin Aniverm-2.0% - M. B. Musaev; V. V. Zashchepkina; I. Kh. Shahbiev (Российский паразитологический журнал, 2025)
The purpose of the research is to evaluate embryotoxic and teratogenic effects of the supramolecular complex of ivermectin aniverm-2.0%.Materials and methods. The experiment was conducted on 100 female rats weighing 180–200 g that were kept in the vivarium of the VNIIP – FSC VIEV. The experimental rats were divided into groups of 8 animals each. The supramolecular complex of ivermectin aniverm-2.0% was administered to inbred pregnant female rats orally in the suspension formulation using an intragastric catheter three times in increased doses. The 1st group pregnant females were administered a total dose of aniverm-2.0% for the first 6 days which was 3 times higher than the therapeutic dose (3.6 mg/kg) by the active substance, and 180 mg/kg by the drug. The 2nd group animals were given the ivermectin substance in a similar dose of 3.6 mg/kg in the suspension formulation on starch paste on the first day of pregnancy. The 1st group rats were given a total dose of aniverm-2.0% increased to 3-fold, equal to 7 days (7–13 days), at a dose of 4.2 mg/kg by the active ingredient, and 210 mg/kg by the drug, and the 2nd group rats received a similar dose of the ivermectin substance of 4.2 mg/kg in the suspension formulation on starch paste on day 7 of pregnancy. On day 14 (days 14–19), the 1st group rats were administered a total dose of aniverm-2.0% for 6 days for the third time at a dose of 3.6 mg/kg by the active ingredient, and 180 mg/kg by the drug, and the second group of animals received the substance of ivermectin at a dose of 3.6 mg/kg by the active ingredient in the suspension formulation on starch paste. The female rats from the 3rd control group were administered starch paste of 5–7 mL three times during the same periods of pregnancy as the experimental animals. On day 20 of embryogenesis, all experimental rats were euthanized. In the females, after slaughter and extirpation of the uterus, the number of embryos, resorptions, and corpus luteum in pregnancy in both ovaries was recorded; the craniocaudal embryo dimensions were measured, their weight was recorded, and their sex was determined. The placenta was measured and weighed to calculate the fetoplacental coefficient. Attention was also paid to deformities and developmental anomalies in the embryos. Some of the fetuses were then placed in Bouin's fluid for further examination of the internal organs using the Wilson method. Another part was fixed in 96.0% alcohol to examine the skeletal system and measure bone length using the Dawson method. To assess embryotoxic effects of the drug, preand post-implantation death and total embryonic mortality were recorded. The obtained results were processed statistically.Results and discussion. In the entire pregnancy period, no signs of intoxication were observed in the animals. The animals were active, ate food readily and gained weight well. Macroscopic examination of the internal organs did not reveal any pathological changes. There were no signs of inflammation, deformities or other abnormalities in the embryos and placentas. Aniverm-2.0% in a three-fold increased dose of 0.6 mg/kg with intragastric administration did not exhibit embryotoxic or teratogenic effects in critical periods of embryogenesis.